EFEK CYBERBULLYING TERHADAP PERSEPSI PUBLIK TENTANG IDOLA K-POP DI PLATFORM X: STUDI DENGAN PENDEKATAN TEORI AGENDA SETTING - Akhmad Risky Saufa; Muhammad Agus Humaidi; Ade Nur Atika Sari (Jurnal Riset Multidisiplin Edukasi, 2026)
This study analyzes the phenomenon of cyberbullying against K-pop idols on the X (Twitter) platform and its impact on public perception using the agenda-setting theory. Amid the global popularity of K-pop, social media has become a primary space for interaction between idols and fans; however, it has also triggered serious cyberbullying, which affects the reputation and public image of idols. The purpose of this research is to identify the forms and patterns of cyberbullying directed at K-pop idols on X (Twitter). The data were collected through in-depth interviews and social media content analysis of informants using a descriptive qualitative approach. The informants consisted of K-pop fans aged 17 to 30 who are active on the X platform and have participated in public opinion discussions and related documentation. The findings show that cyberbullying often begins with provocative viral posts (texts, images, and videos) containing negative narratives that spread instantly through features such as quote tweets, replies, and retweets. This rapid dissemination leads to a majority of users cornering idols, often without sufficient evidence. Verbal attacks frequently escalate into physical insults and issues related to mental health. In general, cyberbullying has a significant impact on public perception due to continuous exposure to negative information, shaping public attitudes and responses toward K-pop idols. Agenda-setting theory helps explain how dominant issues on social media can direct public attention and shape the priority of opinions, leading to negative stereotypes and a desire for attention or self-validation. On the other hand, defenders are driven by loyalty and a sense of responsibility to protect their idols, demonstrated through acts of solidarity such as reporting incidents to agencies. This study is expected to enhance understanding of cyberbullying and provide a foundation for more effective prevention strategies.